Safe spaces, support, social capital: a critical analysis of artists working with vulnerable young people in educational contexts - Sellman, Edward (Wiley, 2015)
This article provides a critical and thematic analysis of three research projects involving artists working with vulnerable young people in educational contexts. It argues that artists create safe spaces in contrast to traditional educational activities but it will also raise questions about what constitutes such a space for participants. It will then show that skilled artists often mediate dichotomous pedagogical positions, characterised by competency and performance. It will employ the metaphor of a trellis to illustrate how artists provide flexible structure and support whilst allowing freedom and growth. Finally, it will discuss the social impact of the arts through the lens of social capital theory, highlighting the utility of the approach whilst also indicating areas for critical refinement.